Alien Aeolian Bedforms: A Comparative Sedimentary Analysis of the Dingo Gap Bedform and Hidden Valley Ripple Traverses, Gale Crater, Mars. Issue 8 (30th August 2021) - Bretzfelder, Jordan M.; Day, Mackenzie
Abstract: At the end of January 2014 (Sols 528–540), the Mars Science Laboratory rover Curiosity approached the valley opening known as Dingo Gap. Spanning this gap was an unusual bedform with a maximum height of 1.34 m and a maximum width of ∼8 m. Curiosity encountered, imaged, and successfully traversed this atypical bedform. In August of 2014, Curiosity began to traverse a field of ripples in Hidden Valley, but was forced to abort the attempt due to high wheel slip. The Hidden Valley ripples are ∼1/6 of the height of the Dingo Gap bedform, and yet posed a serious hazard to the rover. Here, we present a sedimentological analysis of the Dingo Gap bedform and the Hidden Valley ripples and discuss how their differences may have impacted rover traversability. The Dingo Gap and Hidden Valley bedforms are morphologically similar to many commonly observed bedforms on Mars that have few clear analogs on Earth, and Curiosity's encounters provide a framework for studying these bedforms in detail. Furthermore, the rover tracks across the bedforms have persisted for >5 Earth years, even through a global dust storm. The longevity of the tracks demonstrates that on multi‐year timescales (a) sediment transport on some Martian bedforms is inactive or slow enough that areas disturbed by the rover are not resurfaced, and (b) the rate of dust deposition on the Martian surface, even after a global dust storm, is too low to create an optically thick layer. Plain Language Summary: The Mars Science Laboratory rover Curiosity has successfully driven across many surfaces on its journey through Gale crater. Here, we focus on two features formed by wind, a ∼1 m bedform (similar to a small dune) located in a valley opening called Dingo Gap, and a field of ∼20 cm sand ripples located in Hidden Valley. Curiosity was able to cross the Dingo Gap bedform, but had to abort its attempt to cross the Hidden Valley ripples. We use images taken by spacecraft in orbit and by Curiosity on its drive to understand the sedimentologic processes which formed these bedforms in order to determine how they are different. These differences impact the ability of a rover to traverse the bedforms in general, and provide insight into how different types of bedforms on Mars have formed. The Mars 2020 Perseverance rover will encounter many bedforms similar to those analyzed here, and the results can aid in drive planning for current and future rover missions. Key Points: Though less than 5 km apart, the bedform at Dingo Gap and the ripples in Hidden Valley exhibit significant differences in activity Sedimentological differences between the bedforms influence their traversability. We suggest strategies for exploration of aeolian features Inactivity in the studied bedforms suggests very little sediment is transported in these dusty regions of Mars